A preparation method of a catalyst for fuel cells using metal anions as active substances, and a preparation method and application thereof

CN116742011BActive Publication Date: 2026-10-23CHONGQING CERITAN NEW MATERIAL TECH RES INST CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210980961.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-16
Publication Date
2026-10-23
Estimated Expiration
2042-08-16

AI Technical Summary

Technical Problem

[0004]为了解决现有技术存在的上述不足,本发明的目的是提供一种以金属阴离子作为活性物质的燃料电池用催化剂的制备方及其制备方法和应用,以解决现有燃料电池用催化剂制备过程碳载体容易团聚、贵金属在碳载体上搭载量低以及不适合大规模生产的问题

Benefits of technology

[0027]本发明通过阴离子多孔树脂对金属进行吸附,在提升活性金属负载量的同时,能够增加金属阴离子的负载稳定性,同时,多孔树脂热处理后形成的碳载体具有较高的孔隙率和较大的比表面积,不仅能够搭载更多的活性金属,而且可以增加反应物向催化层内部扩散的通道数量,能极大减少催化剂用量,从而降低燃料电池生产成本。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003800412560000011
    Figure HDA0003800412560000011
  • Figure HDA0003800412560000012
    Figure HDA0003800412560000012
  • Figure HDA0003800412560000021
    Figure HDA0003800412560000021
Patent Text Reader

Abstract

The application discloses a preparation method of a fuel cell catalyst with metal anions as active substances, and application thereof. The preparation method comprises the following steps: (1) dissolving an anion salt in water, then adding an anion resin for adsorption, and then separating and drying; (2) then adding a silicon-containing compound hydrolyzed under an alkaline condition, and then adding an alkali liquor for hydrolysis; (3) performing heat treatment on the obtained material in step (2) in an inert gas, then performing post-treatment on the heat-treated material, and then washing and drying, so as to obtain the catalyst. The anion resin is used for adsorbing the metal, so that the metal loading capacity is improved, and the metal loading stability is increased. Meanwhile, the carbon carrier formed after the resin heat treatment has high porosity and large specific surface area, so that more active metals can be carried, the number of diffusion channels of reactants to the inside of the catalytic layer is increased, the catalyst consumption is reduced, and the fuel cell production cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of fuel cell technology, specifically relating to a preparation method and application of a fuel cell catalyst using metal anions as active materials. Background Technology

[0002] A fuel cell is an energy conversion device that converts the chemical energy of fuel and oxidant into electrical energy. Due to its advantages such as low pollution and high energy density, it is considered one of the preferred clean and efficient energy conversion devices for future electric vehicles and other civilian applications. The lifespan of the catalyst is one of the core issues restricting the development of fuel cell technology; commonly used catalysts are carbon-supported noble metal catalysts.

[0003] The catalyst support significantly influences catalyst performance. Studies have shown that pure platinum catalysts supported on carbon nanotubes exhibit twice the catalytic performance of commercial Pt / C catalysts. Graphene, a two-dimensional carbon material with a honeycomb structure composed of a single layer of carbon atoms, possesses a larger specific surface area and better electronic conductivity than carbon nanotubes, making it the most ideal catalyst support after carbon black and carbon nanotubes. However, traditional carbon supports have weak anchoring effects on metal salt precursors adsorbed and precipitated on their surfaces. During high-temperature reduction heat treatment, reduced gold particles easily agglomerate, thus reducing catalyst activity. Furthermore, the lack of functional groups on the surface of existing carbon supports makes them difficult to disperse or prone to agglomeration, hindering the mounting of precious metals and resulting in lower activity in the final product due to insufficient precious metal loading. Summary of the Invention

[0004] To address the aforementioned shortcomings of existing technologies, the present invention aims to provide a method for preparing a fuel cell catalyst using metal anions as active materials, along with its application, thereby resolving issues such as easy agglomeration of carbon supports, low loading of precious metals on carbon supports, and unsuitability for large-scale production in existing fuel cell catalyst preparation processes.

[0005] The technical solution of the present invention to solve the above-mentioned technical problems is as follows:

[0006] A method for preparing a fuel cell catalyst using metal anions as the active material includes the following steps:

[0007] (1) Dissolve the anionic salt in water, then add an anionic resin for adsorption, then separate and dry to obtain a resin adsorbed with metal anions.

[0008] (2) The resin adsorbed with metal anions is dispersed in a solvent, and then a silicon-containing compound hydrolyzed under alkaline conditions is added. Then, an alkaline solution is added for hydrolysis. The hydrolysate coats the resin adsorbed with metal anions.

[0009] (3) The material obtained in step (2) is heat-treated in an inert gas, and then the heat-treated material is post-treated, washed and dried to obtain the final product.

[0010] The beneficial effects of this invention are as follows: In preparing the catalyst, the anionic salt is first dissolved in water, and then an anionic porous resin is added. The metal anions are adsorbed by the anionic porous resin, thereby achieving the purpose of loading the metal anions onto the support. This invention uses anionic porous resin as the adsorption support for metal anions. During subsequent heat treatment, it forms porous nitrogen-doped carbon. Compared to the solid carbon supports widely used in existing technologies, the carbon support obtained by this invention has a hollow structure, higher porosity, and a larger specific surface area. This not only allows for the loading of more active metals but also increases the number of channels for reactants to diffuse into the catalyst layer, significantly reducing the amount of catalyst used and thus lowering the production cost of fuel cells.

[0011] In this invention, after the resin adsorbs metal anions, the resin containing adsorbed metal ions is further coated with a silicon-containing compound. The coating not only further improves the adsorption stability of metal anions, but more importantly, the metal nanoparticles loaded on the coated resin are less likely to agglomerate during heat treatment. In addition, volatile substances such as water are also coated in the coating process. During the subsequent heat treatment, the volatile substances volatilize, providing a certain growth space for the catalyst, thereby controlling the particle size of the catalyst.

[0012] Furthermore, the particle size of the anion exchange resin is below 0.25 mm.

[0013] The beneficial effects of the above-mentioned further technical solutions are as follows: controlling the particle size of the anion porous resin can not only increase the specific surface area of ​​the adsorption resin and improve the loading of metal anions, but also regulate the size of the final catalyst.

[0014] Furthermore, in step (1), the mass ratio of anionic salt to anionic resin is 1:5 to 3:1.

[0015] Furthermore, the anionic salt is at least one selected from ammonium molybdate, sodium molybdate, sodium tungstate, ammonium tungstate, sodium cobalt cyanide, potassium cobalt cyanide, sodium ferrocyanide, potassium ferrocyanide, potassium nickel cyanide, potassium hexacyanide nickelate, and potassium manganate.

[0016] Furthermore, in step (1), the adsorption temperature is 15–80℃ and the adsorption time is 3–12h.

[0017] Furthermore, the mass ratio of the silicon-containing compound (calculated as silicon dioxide) to the resin adsorbed with metal ions is 2:1 to 1:2.

[0018] Furthermore, the silicon-containing compound is a silicate, methyl orthosilicate, ethyl orthosilicate, or 3-aminopropyltriethoxysilane.

[0019] Furthermore, the alkaline solution is an ammonia solution with a pH of 9 to 11.

[0020] Furthermore, in step (2), the hydrolysis temperature is 15–80℃ and the hydrolysis time is 3–10h.

[0021] Furthermore, the inert gas is argon or nitrogen.

[0022] Furthermore, in step (3), the heat treatment temperature is 700–1000℃ and the heat treatment time is 6–10h.

[0023] Furthermore, in step (3), the post-treatment involves immersing the heat-treated material in a hydrofluoric acid solution with a concentration of 5-40% and stirring at room temperature for 5-12 hours.

[0024] This invention also discloses a fuel cell catalyst using metal anions as the active material, which is prepared by the above-described method. The fuel cell catalyst using metal anions as the active material in this invention can be represented as: MoC / NC, WC / NC, Fe-NC, Co-NC, Ni-NC, or Mn-NC.

[0025] The present invention also discloses the application of a catalyst for fuel cells using metal anions as active materials, which can be used as a catalyst support or in the application of a non-platinum cathode oxygen reduction catalyst in fuel cells.

[0026] The present invention has the following beneficial effects:

[0027] This invention utilizes anionic porous resin to adsorb metals, thereby increasing the loading capacity of active metals and enhancing the loading stability of metal anions. Furthermore, the carbon support formed after heat treatment of the porous resin has high porosity and a large specific surface area, which not only allows for the loading of more active metals but also increases the number of channels for reactants to diffuse into the catalyst layer, significantly reducing the amount of catalyst required and thus lowering the production cost of fuel cells.

[0028] This invention, through the coating of silicon-containing compounds, avoids the sintering and agglomeration of metal ions while allowing for the control of catalyst size, thus achieving the goal of adjustable catalyst size. Attached Figure Description

[0029] Figure 1 The image shows the XRD pattern of Fe-NC.

[0030] Figure 2 The isothermal N2 adsorption-desorption curves for Fe-NC are shown.

[0031] Figure 3 This is a pore size distribution diagram for Fe-NC.

[0032] Figure 4 This is the SEM image of Fe-NC. Figure 5 The LSV curves for the Fe-NC catalyst are shown. Detailed Implementation

[0033] The examples given below are for illustrative purposes only and are not intended to limit the scope of the invention. Unless otherwise specified, conditions in the examples are performed under standard conditions or as recommended by the manufacturer. Reagents or instruments whose manufacturers are not specified are all commercially available products.

[0034] The anion exchange resins used in this invention include MP62 and D301 resins.

[0035] The electrochemical performance testing conditions for the obtained catalyst in this invention are as follows:

[0036] CV: CV curve of N2-saturated 0.1M HClO4 solution, scan rate 50 mV / s -1 ;

[0037] LSV: LSV curve in O2-saturated 0.1M HClO4 solution, scan rate 10 mV / s -1 1600 rpm;

[0038] CO: 0.1M N2 saturated HClO4 solution at 10mV s -1 The scan rate is used to record CO removal.

[0039] Example 1: Fe-NC catalyst

[0040] A catalyst for fuel cells, Fe-NC, using metal anions as the active material, is prepared through the following steps:

[0041] (1) Take MP62 resin and grind it through a 60-mesh sieve (0.25mm);

[0042] (2) Take 1g of ground MP62 resin, add an appropriate amount of ultrapure water to prepare a solution of 0.1g / mL, then add 3g K3[Fe(CN)6], stir and mix evenly, adsorb at 60℃ for 4h, then centrifuge and dry to obtain resin adsorbed with metal anions.

[0043] (3) Disperse the resin adsorbed with metal anions in ethanol solvent, then add tetraethyl orthosilicate. The mass ratio of the added tetraethyl orthosilicate (calculated as silica, the silica generated after hydrolysis) to the resin adsorbed with metal ions is 1:1. Then add an equal volume of ammonia water with pH=10, and hydrolyze at 60°C for 6 hours. The hydrolysate coats the resin adsorbed with metal anions.

[0044] (4) The product obtained in step (3) is subjected to heat treatment in nitrogen at a temperature of 900°C for 8 hours.

[0045] (5) The heat-treated material is immersed in a 5% hydrofluoric acid solution and stirred at room temperature for 6 hours. Then, it is filtered, washed, dried and ground to obtain the desired catalyst.

[0046] Example 2: Co-NC catalyst

[0047] A fuel cell catalyst, Co-NC, using metal anions as the active material, is prepared through the following steps:

[0048] (1) Take MP62 resin and grind it through a 60-mesh sieve (0.25mm);

[0049] (2) Take 1g of ground MP62 resin, add an appropriate amount of ultrapure water to prepare a 0.1g / mL solution, then add 2g Na3[Co(CN)6], stir and mix evenly, adsorb at 30℃ for 6h, then centrifuge and dry to obtain resin adsorbed with metal anions.

[0050] (3) Disperse the resin adsorbed with metal anions in ethanol solvent, then add tetraethyl orthosilicate. The mass ratio of the added tetraethyl orthosilicate (calculated as silicon dioxide, the silicon dioxide generated after hydrolysis) to the resin adsorbed with metal ions is 1:2. Then add an equal volume of pH=10NH3·H2O solution and stir at 80℃ for 3h to hydrolyze. The hydrolysate coats the resin adsorbed with metal anions.

[0051] (4) The product obtained in step (3) is subjected to heat treatment in nitrogen at a temperature of 700°C for 10 hours.

[0052] (5) The heat-treated material is immersed in a 10% HF solution and stirred at room temperature for 10 hours. Then, it is filtered, washed, dried and ground to obtain the desired catalyst.

[0053] Example 3: Ni-NC catalyst

[0054] A Ni-NC catalyst for fuel cells, using metal anions as the active material, is prepared through the following steps:

[0055] (1) Take D301 resin and grind it through a 60-mesh sieve (0.25mm);

[0056] (2) Take 1g of ground D301 resin, add an appropriate amount of ultrapure water to prepare a 0.1g / mL solution, then add 1g of K2Ni(CN)4, stir and mix evenly, adsorb at 40℃ for 8h, then centrifuge and dry to obtain resin adsorbed with metal anions.

[0057] (3) Disperse the resin adsorbed with metal anions in ethanol solvent, then add tetraethyl orthosilicate. The mass ratio of the added tetraethyl orthosilicate (calculated as silicon dioxide, the silicon dioxide generated after hydrolysis) to the resin adsorbed with metal ions is 1:1. Then add an equal volume of pH=10NH3·H2O solution and stir at 60℃ for 8 hours to hydrolyze. The hydrolysate coats the resin adsorbed with metal anions.

[0058] (4) The product obtained in step (3) is heat-treated in argon gas at a temperature of 900°C for 8 hours.

[0059] (5) The heat-treated material is immersed in a 20% HF solution and stirred at room temperature for 6 hours. Then, it is filtered, washed, dried and ground to obtain the desired catalyst.

[0060] Example 4: Mn-NC catalyst

[0061] A Ni-NCMn-NC catalyst for fuel cells, using metal anions as the active material, is prepared through the following steps:

[0062] (1) Take D301 resin and grind it through a 60-mesh sieve (0.25mm);

[0063] (2) Take 1g of ground D301 resin, add an appropriate amount of ultrapure water to prepare a solution of 0.1g / mL, then add 0.5g potassium manganate, stir and mix evenly, adsorb at 40℃ for 6h, then centrifuge and dry to obtain resin adsorbed with metal anions.

[0064] (3) Disperse the resin adsorbed with metal anions in ethanol solvent, then add tetraethyl orthosilicate. The mass ratio of the added tetraethyl orthosilicate (calculated as silicon dioxide, the silicon dioxide generated after hydrolysis) to the resin adsorbed with metal ions is 0.6:1. Then add an equal volume of pH=10NH3·H2O solution and stir at 60℃ for 10h to hydrolyze. The hydrolysate coats the resin adsorbed with metal anions.

[0065] (4) The product obtained in step (3) is heat-treated in argon gas at a temperature of 1000℃ for 6 hours.

[0066] (5) The heat-treated material is immersed in a 20% HF solution and stirred at room temperature for 6 hours. Then, it is filtered, washed, dried and ground to obtain the desired catalyst.

[0067] Experimental Example

[0068] The performance of the catalyst will be explained using the catalyst prepared in Example 1 as an example.

[0069] Catalyst performance test results as follows Figures 1-5 As shown, where, Figure 1 The XRD pattern of the Fe-NC catalyst is shown. Figure 2 The isothermal N2 adsorption-desorption curves of the Fe-NC catalyst are shown. Figure 3 This is a pore size distribution diagram of the Fe-NC catalyst. Figure 4 The image shows the SEM pattern of the Fe-NC catalyst. Figure 5 The LSV curves for the Fe-NC catalyst are shown.

[0070] The morphology of Fe-NC material was studied by SEM, which showed that Fe-NC material exhibits a porous three-dimensional structure. The XRD pattern showed a diffraction peak at 25.5°, corresponding to the (002) crystal plane of graphitic carbon. The specific surface area and pore structure of Fe-NC were investigated by nitrogen adsorption (BET), and the specific surface area of ​​Fe-NC was found to be 813 m². 2 / g. The half-wave potential is 0.851V, slightly lower than that of the Pt / C catalyst.

[0071] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a fuel cell catalyst using metal anions as the active material, characterized in that, Includes the following steps: (1) Dissolve the anionic salt in water, then add an anion exchange resin for adsorption, then separate and dry to obtain a resin adsorbed with metal anions; the anionic salt is at least one of ammonium molybdate, sodium molybdate, sodium tungstate, ammonium tungstate, sodium cobalt cyanide, potassium cobalt cyanide, sodium ferrocyanide, potassium ferrocyanide, potassium nickel cyanide, potassium hexacyanide, and potassium manganate; (2) The resin adsorbed with metal anions is dispersed in a solvent, and then a silicon-containing compound hydrolyzed under alkaline conditions is added. Then, an alkaline solution is added for hydrolysis. The hydrolysate coats the resin adsorbed with metal anions. The alkaline solution is an ammonia solution with pH=9~11. The hydrolysis temperature is 15~80℃ and the hydrolysis time is 3~8h. (3) The material obtained in step (2) is heat-treated in an inert gas, and then the heat-treated material is post-treated, then washed and dried to obtain the product; the heat treatment temperature is 700~1000℃ and the heat treatment time is 6~10h. The catalyst is MoC / NC, WC / NC, Fe-NC, Co-NC, Ni-NC, or Mn-NC.

2. The preparation method according to claim 1, characterized in that: The anion exchange resin has a particle size of less than 0.25 mm.

3. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of anionic salt to anionic resin is 1:5 to 3:

1.

4. The preparation method according to claim 1, characterized in that: In step (1), the adsorption temperature is 15~80℃ and the adsorption time is 3~12h.

5. The preparation method according to claim 1, characterized in that: The mass ratio of the silicon-containing compound (based on silicon dioxide) to the resin adsorbed with metal ions is 2:1 to 1:2; the silicon-containing compound is a silicate, methyl orthosilicate, ethyl orthosilicate, or 3-aminopropyltriethoxysilane.

6. The preparation method according to claim 1, characterized in that: The inert gas mentioned in step (3) is argon or nitrogen; the post-treatment in step (3) is to immerse the heat-treated material in a hydrofluoric acid solution with a concentration of 5-40% and stir it at room temperature for 5-12 hours.

7. A fuel cell catalyst using metal anions as active materials, prepared by the preparation method according to any one of claims 1 to 6.

8. The application of the fuel cell catalyst with metal anions as active material as described in claim 7 as a catalyst support or a non-platinum cathode oxygen reduction catalyst in a fuel cell.

Citation Information

Patent Citations

  • Catalyst loaded on carbon sphere and preparation method of catalyst

    CN103394354A

  • Silicon dioxide-protected carbon-based catalyst as well as preparation method and application thereof

    CN109675603A